2016
DOI: 10.2188/jea.je20150047
|View full text |Cite
|
Sign up to set email alerts
|

Association of Combined Tobacco Smoking and Oral Contraceptive Use With Cervical Intraepithelial Neoplasia 2 or 3 in Korean Women

Abstract: BackgroundCigarette smoking and oral contraceptive (OC) use have been associated with cervical neoplasia, and the combination of smoking and OC use could influence cervical carcinogenesis. We aimed to assess the joint effect of smoking and OC use on the risk of cervical intraepithelial neoplasia (CIN).MethodsFrom a cohort of human papillomavirus-positive subjects recruited from 6 hospitals in Korea from March 2006 to November 2012, a total of 678 subjects (411 control, 133 CIN 1, and 134 CIN 2 or 3 cases) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 38 publications
2
15
1
8
Order By: Relevance
“…Research in China and worldwide has shown that HR-HPV infection, poor reproductive health, oral contraceptive use, trichomonas vaginitis, and smoking may be risk factors for CIN and cervical cancer 26-28. In the present study, we did not identify vaginitis or contraceptive use as risk factors for CIN.…”
Section: Discussioncontrasting
confidence: 80%
“…Research in China and worldwide has shown that HR-HPV infection, poor reproductive health, oral contraceptive use, trichomonas vaginitis, and smoking may be risk factors for CIN and cervical cancer 26-28. In the present study, we did not identify vaginitis or contraceptive use as risk factors for CIN.…”
Section: Discussioncontrasting
confidence: 80%
“…We believe that the results are shocking, especially for Asians. However, we should note that only three studies were conducted in Asians . Considering that the number of studies on Asian populations was small, this result should be taken with caution.…”
Section: Discussionmentioning
confidence: 85%
“…Therefore, this process resulted in 16 studies being identified as meeting the rigid inclusion criteria (Fig. ) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Já os HPVs de alto risco são representados pelos tipos 16,18,31,33,35,39,45,51,52,56,58,59,66,68,73, sendo que os tipos 16 e 18 são associados, aproximadamente, a 50% das lesões intraepiteliais de alto grau e a 70% dos casos de câncer cervical (TROTTIER;FRANCO, 2006;NOWAKOWSKI et al, 2015;CLIFFORD et al, 2006 SOLOMON et al, 2002;RICHART, 1990 -STORTHZ, 2005;VACCARELLA et al, 2006;BOSCH et al, 2006;CHELIMO et al, 2013 (MARKS et al, 2015;MORENO et al, 2002). Alguns estudos corroboram com esses achados, encontrando associação no uso prolongado de contraceptivos orais e a persistência da infecção pelo HPV e o desenvolvimento de lesões cervicais (BOSCH et al, 2006;ROURA et al, 2016;OH et al, 2016;RUGGERI et al, 2015) Estudos relacionam o uso prolongado de contraceptivos hormonais e lesões cervicais mostrando basicamente três hipóteses: uma contribuindo para ectopia cervical ("ferida") e aumentando a aquisição de HPV, outra modulando a resposta imune do hospedeiro ao HPV, facilitando a persistência da infecção e desenvolvimento de lesões pré-cancerígenas, e uma terceira através do aumento da atividade transformadora dos oncogenes do HPV, bem como a contribuição para o aumento da expressão destes, principalmente E6 e E7, podendo interferir na resolução da infecção e das lesões na cérvix de mulheres jovens por meio da ligação de progesterona e de receptores de glicocorticóides à LCR do HPV (MARKS et al, 2011;PINTO;TÚLIO;CRUZ, 2002;KWASNIEWSKA et al, 2011). ALMONTE et al, 2008;…”
Section: Fases Da Doençaunclassified